CUSTOMS TARIFFS AND THE POLICY OF CUSTOM TARIFFS IN THE FUNCTION OF THE REALIZATION OF REGIONAL ECONOMIC INTEGRATIONS: THE EXAMPLE OF THE EUROPEAN UNION - Vranješ, Mile (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Custom tariffs and the policy of custom tariffs have always been important instruments in the protection of domestic production from foreign competition, though the more in the past, the less in today’s global economic environment. The idea of protectionism in international trade hasn’t evaded the European Union either. The European Union has a common protectionist policy against countries that are not member to it. The agricultural production and the policy of administrative levies on the import of agricultural products pertain to the area that enjoys the highest degree of protection. The realization of such protectionist policy makes the international trade less free, while the free movement of goods is quintessential to the economic growth of the European Union, other regional economic integrations, individual countries and the society as such. The World Trade Organization, which imposes its own rules on the international trade, the creation of regional economic organizations in today’s environment of international trade and free-trade agreements between individual states shrank to minimal the diapason of various protectionist measures and instruments. The decline of the idea of protectionism in international trade is evidenced by data on the share of the customs tariffs in the total fiscal revenues of the European Union and of the GDP of the member states. Namely, the fiscal impact of custom tariffs for some years shows a descending tendency, above all due to the process of globalization in foreign trade and liberalization at the scale of global economy. The European Union will be able to facilitate the development of the regional economic integrations only through the liberalization of foreign trade, because the idea of protectionism in international trade doesn’t have perspectives on the long run.